Changes to the national strategies, plans and guidelines for the treatment of hepatitis C in people who inject drugs between 2013 and 2016: a cross-sectional survey of 34 European countries - Mojca Maticic; Jerneja Videcnik Zorman; Sergeja Gregorcic; Eberhard Schatz; Jeffrey V. Lazarus (BMC, 2019)
Abstract Background Hepatitis C virus (HCV) infection is the leading cause of cirrhosis, end-stage liver disease and hepatocellular carcinoma (HCC) worldwide. In Europe, people who inject drugs (PWID) represent the majority of HCV infections, but are often excluded from treatment. The aim of this study was to report on national HCV strategies, action plans and guidelines in European countries that include HCV treatment for the general population as well as for PWID. Data on access to direct-acting antivirals (DAAs) were also collected. Methods In 2016, 38 non-governmental organisations, universities and public health institutions that work with PWID in 34 European countries were invited to complete a 16-item online survey about current national HCV treatment policies and guidelines. Data from 2016 were compared to those from 2013 for 33 European countries, and time trends are presented. Differences in the data were analysed. Data from 2016 on general access to DAAs in PWID are presented separately. Results The response rate was 100%. Fourteen countries (42%) reported having a national HCV strategy covering HCV treatment; 12 of these addressed HCV treatment for PWID. Respondents from ten countries (29%) reported having a national HCV action plan. PWID were specifically included in seven of them. Twenty-nine countries (85%) reported having national HCV treatment guidelines. PWID were specifically included in 23 (79%) of them. Compared to 2013, respondents reported that an additional seven countries (25%) had national strategies, an additional eight countries (29%) had action plans and an additional six countries (19%) had HCV treatment guidelines. However, PWID were not included in two, four and six of those countries, respectively. DAAs were reported to be available in 91% of the study countries, with restrictions reported in 71% of them. Conclusion Respondents reported that fewer than half of the European countries in this study had a national HCV strategy and/or action plan, with even fewer including PWID. However, when compared to 2013, the number of such countries had slightly increased. Although PWID are often addressed in clinical guidelines, strategic action is needed to increase access to HCV treatment for this group and the situation should be regularly monitored.